Produk Interior Berbasis Budaya Kalimantan dengan Memanfaatkan Material Rotan - Shela Tanjaya; Laksmi Kusuma Wardani; M. Taufan Rizqy (Intra, 2018)
Rattan is a material that widely found in Indonesia, especially in Borneo (Kalimantan). In the design, rattan is used as the main material for the product. The product was a furniture set for commercial building, especially cafe. It was designed based on the needs of commercial buildings development and considered as a good opportunity for commercial building product. The target market for this design is the middle-upper class in Kalimantan. The design was inspired by the floating market, which was a local culture of South Kalimantan and the icon of Banjarmasin. The design method adopts some steps of design thinking such as understanding, observe, frame and reframe, ideate, prototype, and test. The dynamic move is a concept that was adapted from the floating market in Kalimantan. The resulting products which are bench, stool, coffee table, and dining chair, show an innovative and dynamic shape which could give a movement impression.